2019
DOI: 10.1002/adfm.201902582
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Nanoparticle‐Seeded Catalytic Nucleation Kinetics of Perovskite Solar Cells by Time‐Resolved GIXS

Abstract: Recently, a new seeding growth approach for perovskite thin films is reported to significantly enhance the device performance of perovskite solar cells. This work unveils the intermediate structures and the corresponding growth kinetics during conversion to perovskite crystal thin films assisted by seeding PbS nanocrystals (NCs), using time-resolved grazing-incidence X-ray scattering. Through analyses of time-resolved crystal formation kinetics obtained from synchrotron X-rays with a fast subsecond probing tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Among various techniques, time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) is a mature and powerful one to study the structural transitions occurring in perovskite materials during printing, spin coating and during temperature annealing. [ 25–27 ] Poister et al monitored changes in the formation of crystalline phase under varying process conditions in real‐time during film growth by X‐ray diffraction and revealed the importance of post annealing treatment. [ 22 ] Hu et al revealed the material transformation pathways and the morphology formation mechanism of Pb‐based perovskites from precursor solution to polycrystalline films over relevant temperature and time scales by using 2D grazing incidence x‐ray diffraction (2D‐GIXD).…”
Section: Introductionmentioning
confidence: 99%
“…Among various techniques, time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) is a mature and powerful one to study the structural transitions occurring in perovskite materials during printing, spin coating and during temperature annealing. [ 25–27 ] Poister et al monitored changes in the formation of crystalline phase under varying process conditions in real‐time during film growth by X‐ray diffraction and revealed the importance of post annealing treatment. [ 22 ] Hu et al revealed the material transformation pathways and the morphology formation mechanism of Pb‐based perovskites from precursor solution to polycrystalline films over relevant temperature and time scales by using 2D grazing incidence x‐ray diffraction (2D‐GIXD).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, to produce the black phase of FAPI perovskite an annealing after spin coating at 165-185 °C is needed, but the addition of PbS reduces dramatically the annealing temperature to obtain the black phase of FAPI, to values as low as 85 °C for a concentration of PbS/FAPI QDs in solution of 5mg/ml, see Supporting Video 1, and annealing times as short as 10 minutes. The presence of PbS accelerates 45 the FAPI black phase crystallization, not just for FAPI but for reported halide perovskites, reducing radically both the self-assembly time and temperature. [16][17][18] The annealing time for the crystallization of the FAPI black phase presents a dependence on the QDs concentration.…”
mentioning
confidence: 99%
“…The latter is also likely related to the mild annealing conditions observed in our experiments. The low annealing temperature indicates that PbS QDs are acting as catalysts, 45 regardless of the size and concentration, that reduce the activation energy required to attain the metastable black phase. It is then plausible that the strong PbS−black FAPI bonds are stabilizing the transition state of the reaction path.…”
mentioning
confidence: 99%
“…As shown in Fig. 2e, the n-value of the fumigated film (0.025) is significantly smaller than the nvalue of the reference one (0.412), suggesting a large nucleation barrier enabled by fumigation [23]. Combining classical nucleation theory, we are able to conjecture a ripening model for colloidal perovskites under routine and fumigated conditions.…”
Section: Articlesmentioning
confidence: 64%
“…To quantitively evaluate the early-stage nucleation rate of colloidal perovskite films, we use the Sharp-Hancock presentation which is described by the relation between the CPS peak intensity (α) and monitoring time (t) [23]:…”
Section: Resultsmentioning
confidence: 99%